2007
DOI: 10.17221/2274-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting ewe's milk fat and protein content and relationships between milk yield and milk components

Abstract: Test-day records of purebred Tsigai, Improved Valachian and Lacaune ewes were used to analyse the effect of environmental factors on milk fat and protein content. There were 121 424 and 121 158 measurements of fat and protein content for Tsigai, 247 742 and 247 606 measurements of fat and protein content for Improved Valachian and 2 194 measurements of fat and protein content for Lacaune ewes lambing between 1995 and 2005. Overall means and standard deviations for fat and protein content were 7.77 ± 1.606% and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
35
2
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 18 publications
11
35
2
3
Order By: Relevance
“…The average DMY of the Bovec (1 090 g), Improved Bovec (1 010 g) and Istrian Pramenka (731 g) sheep population in our study was much lower than DMY of East Friesian dairy breed (2 330 g) reported by Hamann et al (2004). Daily milk yield in breeds B and IB was comparable to DMY in Churra (1 008 In general, the average FC and PC in all three Slovenian breeds were lower in comparison to the previously mentioned sheep breeds observed by Ploumi et al (1998), Carta et al (2001 and Oravcová et al (2007). Contrary, all three observed breeds had higher FC and PC in milk than East-Friesian sheep reported by Hamann et al (2004).…”
Section: Discussionmentioning
confidence: 59%
“…The average DMY of the Bovec (1 090 g), Improved Bovec (1 010 g) and Istrian Pramenka (731 g) sheep population in our study was much lower than DMY of East Friesian dairy breed (2 330 g) reported by Hamann et al (2004). Daily milk yield in breeds B and IB was comparable to DMY in Churra (1 008 In general, the average FC and PC in all three Slovenian breeds were lower in comparison to the previously mentioned sheep breeds observed by Ploumi et al (1998), Carta et al (2001 and Oravcová et al (2007). Contrary, all three observed breeds had higher FC and PC in milk than East-Friesian sheep reported by Hamann et al (2004).…”
Section: Discussionmentioning
confidence: 59%
“…In contrast to previous studies of Oravcová et al (2006Oravcová et al ( , 2007, coefficients of Ali and Schaeffer (1987) lactation curve were not considered nested within parities and only one lactation curve for each milk trait in each breed was estimated here. This approach appeared to describe milk traits according to stage of lactation sufficiently, though some limitations to describe the beginning and the end of lactation curves occurred.…”
Section: Resultsmentioning
confidence: 99%
“…The AC method stands for corrected monthly test for evening/morning differences, taking into account the total volume of milk produced by the whole flock over the two milkings concerned (ICAR, 2011). Milk fat and protein content were determined using the automated infrared method and apparatus calibrated against known sample standards (Oravcová et al, 2007). The analysis of daily milk yield was based on 188403 (Tsigai) and 352094 (Improved Valachian) test-day records; at least three test-days per lactation and four flock-test-day measurements were required.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations